The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13042063
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of On-Farm Anaerobic Digestion System Using Attached-Biofilm Reactor in the Dairy Industry

Abstract: In this study, a techno-economic assessment of an on-farm biogas system using an anaerobic biofilm reactor utilizing cow manure as a fermentation substrate was evaluated. A projection model was developed using Microsoft Excel software with three outputs, the size and dimension of a bioreactor, experimental microbial kinetic studies, and the economic studies based on the experimental results. Characterization analysis of cow manure wastewater showed the total solid (TS), total volatile solid (TVS), total carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The sum of fixed capital investment (FCI), cost of operational labor (COL), cost of utilities (CUT), cost of waste treatment (CWT), and cost of raw material (CRM) represents the total annual cost for carrying out the AD of jabuticaba by-product. In general, the results showed that the management of jabuticaba by-product with the simulated small-scale AD process can be considered a low-cost process for properly disposing waste from industrial processing [37]. The total cost was higher for Scenario 2 (9034.76 USD y −1 ), especially because this scenario presented high FCI (4990.80 USD y −1 ).…”
Section: Cost Discriminationmentioning
confidence: 89%
“…The sum of fixed capital investment (FCI), cost of operational labor (COL), cost of utilities (CUT), cost of waste treatment (CWT), and cost of raw material (CRM) represents the total annual cost for carrying out the AD of jabuticaba by-product. In general, the results showed that the management of jabuticaba by-product with the simulated small-scale AD process can be considered a low-cost process for properly disposing waste from industrial processing [37]. The total cost was higher for Scenario 2 (9034.76 USD y −1 ), especially because this scenario presented high FCI (4990.80 USD y −1 ).…”
Section: Cost Discriminationmentioning
confidence: 89%
“…A general analysis of most studies conducted on AD of farm waste [11][12][13][14][15] indicates that older studies focused on understanding the process fundamentals while recent studies focused on improving efficacy. Moreover, the few reviews published on the subject mainly report on the different aspects of AD (Tab.…”
Section: Introductionmentioning
confidence: 99%